Comparison Amino Acid Profile of Pearl Lobster (Panulirus ornatus) Fed with Combination of Fish Meal and Mollusc Meal - Muskita, Wellem Henrik; Kurnia, Agus; Subandiyono, Subandiyono; Yusnaini, Yusnaini; La Usaha, La Usaha; Suaida, Suaida; Effendy, Irwan Junaidi; Hamzah, Muhaimin; Munadi, La Ode Muh; Anwar, Asni (Departemen Akuakultur FPIK UNDIP, 2024)
AbstractPanulirus ornatus is a vital fishery commodity that has high economic value. The research aims to examine the growth, amino acid profile, and intestinal histology of Panulirus ornatus fed a combination of fish meal and mollusk meal using a randomized block design (RBD) method with four treatments and three replications fed with four formulations for 50 days of maintenance. Four formulated feeds contained 20% sardine fish meal + 20% jackmackerel fish meal (treatment A), 10% mangrove snail meal + 15% golden snail meal + 15% mussel clam meal (Treatment B), 15% mangrove snail meal + 10% golden snail flour + 15% mussel clam flour (Treatment C), and 15% mangrove snail flour + 15% golden snail flour + 10% musselclam flour (Treatment D) were given to pearl lobsters once a day at a dosage of 3% of their weight body. Kepah cockle flour has more essential and nonessential amino acids than mangrove and golden snail flour. Mangrove snail flour has higher histidine levels than golden and kepah cockle flour. The results of the amino acid analysis of the test feed showed that the total essential amino acids and total nonessential amino acids in all test feeds showed the same amount, namely 13,0 -14,0%.The findings concluded that feed containing The combination of mollusks flour is more suitable than the combination of fish flour for the growth and amino acid needs of pearl lobsters. Keywords: Amino Acids, Pearl Lobster, Mollusc Flour